2017
DOI: 10.3343/alm.2017.37.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Optimizing Tuberculosis Treatment: Therapeutic Drug Monitoring, Pharmacogenetics, and Nutritional Status Considerations

Abstract: Although tuberculosis is largely a curable disease, it remains a major cause of morbidity and mortality worldwide. Although the standard 6-month treatment regimen is highly effective for drug-susceptible tuberculosis, the use of multiple drugs over long periods of time can cause frequent adverse drug reactions. In addition, some patients with drug-susceptible tuberculosis do not respond adequately to treatment and develop treatment failure and drug resistance. Response to tuberculosis treatment could be affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 76 publications
(114 reference statements)
2
38
1
1
Order By: Relevance
“…A multivariate logistic regression analysis indicated that the patient's HIV status, TB regimen, the type DOT provider, prior cotrimoxazole prophylaxis, sputum conversion at 2 months and the region, were significant predictors of TB treatment outcomes ( Table 2). Our findings though differ from other studies that found that patient's demographics including their age 41,46 and male-gender 27,[46][47][48][49] , as well as the TB diagnostic category, and level of health facility care, were significant predictors of TSR. However, our findings are similar to others that have reported a positive HIV status and sputum non-conversion at month 2 as important risk factors for poor treatment outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A multivariate logistic regression analysis indicated that the patient's HIV status, TB regimen, the type DOT provider, prior cotrimoxazole prophylaxis, sputum conversion at 2 months and the region, were significant predictors of TB treatment outcomes ( Table 2). Our findings though differ from other studies that found that patient's demographics including their age 41,46 and male-gender 27,[46][47][48][49] , as well as the TB diagnostic category, and level of health facility care, were significant predictors of TSR. However, our findings are similar to others that have reported a positive HIV status and sputum non-conversion at month 2 as important risk factors for poor treatment outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have associated high rates of death and defaulting among TB patients to be due to the inappropriate choice of TB regimens 37,38 , HIV co-infection 39,40 , adverse drug effects [41][42][43] and the lack of screening and monitoring systems 6,18,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also have shown an effect of NAT2 genotype on INH efficacy31, 32 and pharmacogenetic-based therapy for tuberculosis has been proposed33, 34, 35, 36, 37. Isoniazid concentrations of 3–6 μg/mL are the usual target for tuberculosis therapy36, 37. Our findings in cryopreserved human hepatocytes following incubations with 12.5 (1.71 µg/mL) and 100 (13.7 µg/mL) µmol/L INH reflect this therapeutic range of INH concentrations supporting use of NAT2 genotype in isoniazid dosing strategies ( i.e ., rapid > intermediate> slow acetylators).…”
Section: Discussionmentioning
confidence: 99%
“…It causes illness in millions of people each year and in 2015 was one of the leading 10 causes of death worldwide, ranking above HIV/AIDS as one of the leading causes of death from an infectious disease (1). Although TB is largely a curable disease, it remains a major cause of morbidity and mortality worldwide (9). Sputum smear microscopy was developed more than 100 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies in Iran on a larger number of patients, considering the clinical diseases, quantity and quality of sputum, culture sputum, PCR, and viability stain microscopy with fluorescein diacetate are suggested. Management of comorbid conditions including nutritional status could improve anti-tubercular treatment responses (9).…”
Section: Discussionmentioning
confidence: 99%